2015
DOI: 10.4141/cjps-2014-422
|View full text |Cite
|
Sign up to set email alerts
|

Weed control and crop tolerance of micro-encapsulated acetochlor applied sequentially in glyphosate-resistant soybean

Abstract: . 2015. Weed control and crop tolerance of micro-encapsulated acetochlor applied sequentially in glyphosate-resistant soybean. Can. J. Plant Sci. 95: 973Á981. Acetochlor, an acetamide herbicide, has been used for many years for weed control in several crops, including soybean. Micro-encapsulated acetochlor has been recently registered for preplant (PP), pre-emergence (PRE), and post-emergence (POST) application in soybean in the United States. Information is not available regarding the sequential application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 28 publications
4
35
2
Order By: Relevance
“…PRE herbicides, also referred to as soil residual herbicides, are applied to the soil after crop planting but before emergence for controlling germinating or emerging weed seedlings. Soil-residual PRE herbicides generally lose their residual activity in the soil in 30–50 days; however, most POST herbicides commonly applied in maize have minimal to no soil residual activity (Jhala et al, 2015 ; Wiggins et al, 2015 ). Moreover, late-emerging Palmer amaranth plants often escape POST herbicide applications and produce seeds, leading to the replenishment of the soil seedbank and ensuring weed infestations for the next several seasons (Keeley et al, 1987 ).…”
Section: Introductionmentioning
confidence: 99%
“…PRE herbicides, also referred to as soil residual herbicides, are applied to the soil after crop planting but before emergence for controlling germinating or emerging weed seedlings. Soil-residual PRE herbicides generally lose their residual activity in the soil in 30–50 days; however, most POST herbicides commonly applied in maize have minimal to no soil residual activity (Jhala et al, 2015 ; Wiggins et al, 2015 ). Moreover, late-emerging Palmer amaranth plants often escape POST herbicide applications and produce seeds, leading to the replenishment of the soil seedbank and ensuring weed infestations for the next several seasons (Keeley et al, 1987 ).…”
Section: Introductionmentioning
confidence: 99%
“…At 14 DALPOST, POST-only treatments of imazethapyr plus fomesafen plus glyphosate plus acetochlor fb lactofen plus glyphosate reduced common waterhemp density to 30 plants m −2 , which was comparable to several PRE fb POST herbicide programs, including saflufenacil plus imazethapyr, S -metolachlor, or pendimethalin plus metribuzin fb fomesafen plus glyphosate (Table 4). The residual activity of micro-encapsulated acetochlor tank-mixed with other herbicides in POST herbicide programs can suppress common waterhemp emergence later in the growing season (Jhala et al 2015). Similarly, Cahoon et al (2015) and Sarangi et al (2013) reported that micro-encapsulated acetochlor applied alone or tank-mixed with other residual herbicides showed >90% control of common waterhemp and Palmer amaranth, reducing plant density significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, glyphosate has become the most commonly used herbicide in agriculture worldwide (Dill et al 2010;Duke and Powles 2008). Moreover, glyphosate-resistant crop technology has encouraged no-till or conservation tillage practices where weed control is primarily based on the application of herbicides (Coffman and Frank 1991;Gianessi 2005;Jhala et al 2014a;Norsworthy et al 2012), which is believed to aid in the shift towards small-seeded broadleaf weed species such as common waterhemp (Culpepper 2006;Legleiter and Bradley 2008;Owen 2008).…”
mentioning
confidence: 99%
“…Post-emergence herbicide such as bentazone has been registered for weed control in soybean. A pre-emergence followed by post-emergence herbicide program provided better weed control in soybean compared with solely post-emergence herbicide program in several studies in the United States (Taylor-Lovell et al, 2002;Jhala et al, 2015). (Zarco-Tejada et al, 2000) remark that chlorophyll leaves are one of the most important indicators of environmental stresses on the plant and they believed that the amount of chlorophyll in plants under stress and the total absorption of light by the plant could be reduced.…”
Section: Introductionmentioning
confidence: 99%